Hakekat Peraturan Pemerintah Pengganti Undang-Undang (PERPPU) Dalam Peraturan Perundang-Undangan di Negara Republik Indonesia - Dwiyanti, Asti (Jurnal Litigasi Amsir, 2023)
This study is intended to investigate the size or reason for the issuance of a PERPPU by the President, as well as the nature or content of a state crisis that creates a convincing state of emergency. This research uses the Literature Review Comparative Study procedure, using secondary information. In granting the PERPPU, the President’s power appears to be "strong", no mediation can be carried out by any agency until the opportunity comes for deliberations in the DPR to decide whether the PERPPU is ratified or dissolved. This examination raises issues, first, what are the dimensions or reasons for the establishment of a PERPPU by the President? Second, what is the nature or content of the country’s crisis that makes a state of emergency compelling? The inspection technique relies on essential and selected halal materials, assisted by written studies and using juridical methodologies. The consequences of closing the review are, first, the size or reason for the formation of a PERPPU by the President depends on very unexpected (strange) conditions or events from a country as a state crisis. Second, the nature or content of the country’s crisis which makes it a convincing state of emergency consists of 3 (three) components, namely the first component is a dangerous hazard; second, the need component that requires, and third, the limited time component that can be accessed.